Subjetivación política de los estudiantes chilenos - Marcela Sandoval (Amnis)
Based on the political viewpoint of Jacques Rancière, the following article is an invitation to reflect upon the events that have taken place in Chile since 2011, currently known as the « student movement ». To start with, the focus will be centered on developing an understanding of Jacques Rancière’s concept of « political subjectivation ». Having examined the concept, the focal point will then be placed on the conflict that has emerged from the student demands in Chile. We suggest that there is a process of political subjectivation within the student movement, according to Rancière’s definition of the concept. Our hypothesis is that the demands for quality public education that is free of cost is the result of the process of students becoming and establishing a political subject.